دور المدرسين لدوافع رغبة الطلبة في تعليم اللغة العربية - Banta Ali ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2017)
Teacher is one of human components in teaching and learning process that plays critical role in creating quality human resource for the development sector. In another definition, teacher is a person who teaches and performs studies focusing on applied activities by experimenting an idea into practice or real situations in a micro scale in which the activities are expected to develop and improve the quality of teaching and learning process within educational sector and to perform advancement in social sector. From another perspective, a teacher as the main principle in educational sector can predict a successful education for the future generations because the development and the prosperity of a nation is fostered through higher education.